Chaos, Periodicity, and Quasiperiodicity in a Radio-Physical Oscillator - Wiggers V.* (2017)
© 2017 World Scientific Publishing Company.We report parameter planes displaying dynamical behaviors of a radio-physical oscillator system, which is modeled by a set of four-parameter three autonomous first-order nonlinear ordinary differential equations. Each parameter plane is numerically computed, and the dynamical behavior of each point is characterized by using the respective Lyapunov exponents spectrum. Chaotic, periodic, and quasiperiodic regions are therefore bounded in parameter planes of a radio-physical oscillator system.